THE DYNAMICS OF LOCAL GOODS TRADE AND IMPORTS IN THE SERIKIN CROSS-BORDER MARKET: AN ANALYSIS OF INDONESIA-MALAYSIA ECONOMIC INTERACTIONS THROUGH LITERATURE REVIEW - Gunawan Widjaja; Wagiman Wagiman (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the dynamics of local and imported goods trade in the Serikin Cross-Border Market located on the border between Indonesia and Malaysia. This market serves as a dynamic centre of economic interaction, where business actors from both countries establish close trade relations, both formal and informal. A literature review identified factors influencing these economic interactions, including the role of local and imported products, regulatory challenges, and socio-economic impacts on border communities. The findings reveal that the Serikin Market is not only a place for goods transactions but also a medium for strengthening bilateral relations and empowering the local economy. Optimising the management of this market heavily depends on policy synergy between Indonesia and Malaysia, as well as innovation by business actors on the ground.